Is Didymosphenia geminata an introduced species in New Zealand? Evidence from trends in water chemistry, and chloroplast DNA. Issue 2 (12th December 2017) - Kilroy, Cathy; Novis, Phil
Abstract: Defining the geographic origins of free‐living aquatic microorganisms can be problematic because many such organisms have ubiquitous distributions, and proving absence from a region is practically impossible. Geographic origins become important if microorganisms have invasive characteristics. The freshwater diatom Didymosphenia geminata is a potentially ubiquitous microorganism for which the recent global expansion of nuisance proliferations has been attributed to environmental change. The changes may include declines in dissolved reactive phosphorus (DRP) to low levels (e.g., <2 mg/m 3 ) and increases in dissolved inorganic nitrogen (DIN) to >10 mg/m 3 because both these nutrient conditions are associated with nuisance proliferations of D. geminata . Proliferations of D. geminata have been observed in South Island, New Zealand, since 2004. We aimed to address the ubiquity hypothesis for D. geminata in New Zealand using historical river water nutrient data and new molecular analyses. We used 15 years of data at 77 river sites to assess whether trends in DRP or DIN prior to the spread of D. geminata were consistent with a transition from a rare, undetected, species to a nuisance species. We used new sequences of chloroplast regions to examine the genetic similarity of D. geminata populations from New Zealand and six overseas locations. We found no evidence for declines in DRP concentrations since 1989 that could explain the spread of proliferations since 2004. At some affected sites, lowest DRP occurred before 2004. Trends in DIN also did not indicate enhanced suitability for D. geminata . Lack of diversity in the chloroplast intergenic regions of New Zealand populations and populations from western North America is consistent with recent dispersal to New Zealand. Our analyses did not support the proposal that D. geminata was historically present in New Zealand rivers. These results provide further evidence countering proposals of general ubiquity in freshwater diatoms and indicate that, as assumed in 2004, D. geminata is a recent arrival in New Zealand. Abstract : Defining the geographic origins of free‐living aquatic microorganisms can be problematic but is important when the organism is invasive and adversely affects native ecosystems. The worldwide expansion of nuisance proliferations of freshwater diatom Didymosphenia geminata in the past two decades has been attributed to environmental change (declining phosphorus levels). We provide evidence, using long‐term DRP data and molecular analyses, that this species was introduced to New Zealand's South Island, justifying its treatment there as an invasive species.